A rapid technique for assessing the moisture ingress susceptibility of plastic-encapsulated integrated circuits - Chwastek, E. J.; Shaw, R. N. (Quality and reliability engineering international, 1987)
The equipment and associated methodology of a new technique for checking the susceptibility of plastic‐encapsulated ICs to moisture ingress is presented. The basis of the new technique is to immerse unbiased ICs in a salt solution and to subject them to high temperatures (in the range 120°C to 175°C) and to high pressures (2 to 9 atmospheres). At the highest temperature, results can be obtained within a few hours, although a 20 h test at 165°C is suggested as a screen for components. The test is extremely simple to carry out and a testing facility can be quickly established. Using CMOS components from five different vendors, good agreement has been obtained between the results from the new test and the results from a biased 85°C/85 percent RH test.